1997
DOI: 10.1080/10835547.1997.12090866
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Foreclosure Status on Residential Selling Price: Comment

Abstract: In this comment we examine the conclusion by Forgey, Rutherford and VanBuskirk (1994) ''that the foreclosed properties sold at a 23% discount,'' using a sample of nearly 2,000 residential property sales from the Las Vagas, Nevada area. We found that when not controlling for location with a set of dummy variables for zip codes, HUD foreclosed properties sold for between 12.18% and 13.96% below a random sample of properties not within one block of foreclosed properties. When controlling for location, using a set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 5 publications
3
17
0
Order By: Relevance
“…Their results show an average foreclosure discount of 23%, consistent with the previous findings in Shilling et al (1990). Carroll et al (1997) questioned Forgey et al's (1994) findings, arguing that the discount rate observed in the latter study was due to a failure to adequately control for the location and neighborhood characteristics of the foreclosed properties. The authors replicated Forgey et al's (1994) study by using similar models to control for the effects of location and neighborhood condition in a sample of 1,974 single-family property sales between 1990 and 1993 in Las Vegas, Nevada.…”
Section: Foreclosure and Disposition Optionssupporting
confidence: 79%
See 2 more Smart Citations
“…Their results show an average foreclosure discount of 23%, consistent with the previous findings in Shilling et al (1990). Carroll et al (1997) questioned Forgey et al's (1994) findings, arguing that the discount rate observed in the latter study was due to a failure to adequately control for the location and neighborhood characteristics of the foreclosed properties. The authors replicated Forgey et al's (1994) study by using similar models to control for the effects of location and neighborhood condition in a sample of 1,974 single-family property sales between 1990 and 1993 in Las Vegas, Nevada.…”
Section: Foreclosure and Disposition Optionssupporting
confidence: 79%
“…After controlling for the property condition, their results revealed discounts of 5.6% for short sale, 10.3% for properties under foreclosure, and 13.5% for REO properties, all relative to a no-default normal market sale (Clauretie & Daneshvary, 2011). The magnitude of the foreclosure effect is similar to prior findings by Carroll et al (1997), with the magnitude of the foreclosure discount ranging between 8.5% and 9.7%. Richardson (2012) investigated the divestiture of distressed commercial real estate in a sample of 18,751 office building transactions spanning the period from 2006 to 2010.…”
Section: Foreclosure and Disposition Optionssupporting
confidence: 57%
See 1 more Smart Citation
“…Among the suitable empirical SD studies for FC estimation are Shilling et al (1990), Forgey et al (1994), Hardin and Wolverton (1996), Carroll et al (1997), and Campbell et al (2011). The first four of these studies generate estimates for s based on small data samples from different geographical locations over somewhat different time intervals.…”
Section: Quantifying Individual Model Input Parametersmentioning
confidence: 99%
“…Several researchers have found that mortgage defaults and the resulting property foreclosures generate a discount of the auction price of the foreclosed property of 7% to 26%, depending on its location within the United States ( e.g ., Shilling, Benjamin and Sirmans 1990, Forgey et al . 1994, Hardin and Wolverton 1996, Springer 1996, Carroll, Clauretieand and Neill 1997, Pennington‐Cross 2006, Clauretie and Daneshvary 2009, Zhou et al . 2015).…”
Section: Introductionmentioning
confidence: 99%